The effect of murottal al-quran surah al-mulk therapy on the sleep quality of babies aged 0-6 months - Setyaningsih, Erna (Link Journal of Midwivery, 2026)
Introduction: There are quite a lot of babies who experience sleep problems in Indonesia, namely around 44%. However, almost or even more than 72% of parents do not consider sleep disturbances in babies as a problem. In fact, sleep problems can interfere with the baby's growth, cause vulnerable immune function, and disrupt the regulation of the endocrine system. Sleep disorders in babies are more recommended for non-pharmacological treatment, namely music therapy. One of the music therapies is listening to murottals of the Al-Qur'an surah Al-Mulk to improve the quality of baby’s sleep. Objective: The purpose of this study is to determine the effect of murottal Al-qur’an surah al-mulk therapy on the sleep quality of babies aged 0-6 months. Method: The research used a pre-experiment method by using one group pre-test and post-test. The research sample used an accidental sampling technique of 5 babies with sleep disorders. The instrument used by researchers was a baby sleep quality questionnaire sheet. Data analysis using test Wilcoxon because of data distributed No normal. Results: There is an effect of Al-Quran surah Al-Mulk murottal therapy on baby sleep quality with a p value of 0.006 (<0.05). The average quality of the baby's sleep before being given Al-Quran murottal therapy was 2.60 and the average after being given Al-Quran murottal therapy was 1.70. Conclusion: There is an influence of Al-Qur'an surah Al-Mulk murrotal therapy on the quality of baby's sleep. This is because murrotal Al-Qur'an therapy can have a calming effect on babies, so that babies can achieve good quality sleep. The research hopes that surah Al-Mulk murrotal therapy can be applied independently and continuously at home so that babies do not have difficulty sleeping.